Cross-national comparisons of the association between alcohol consumption and deliberate self-harm in adolescents. - Rossow, I; Ystgaard, M; Hawton, K; Madge, N; van Heeringen, K; de Wilde, E; DeLeo, D; Fekete, S; Morey, C (2007)
How differences in drinking patterns may affect the impact of alcohol consumption on deliberate self-harm among adolescents is explored in this international comparative study. Schools in Australia, Belgium, England, Hungary, Ireland, the Netherlands, and Norway (N = 30,532) were surveyed. In all countries the risk of deliberate self-harm was significantly elevated among adolescents who reported some or numerous episodes of intoxication, controlling for confounding factors. The results support the assumption that intoxication is significantly related to the association between alcohol consumption and deliberate self-harm in adolescents.